National Accounts Statistics: Analysis of Main Aggregates 2018 - United Nations Department of Economic; Social Affairs (United Nations, 2020)
The National Accounts Statistics: Analysis of Main Aggregates 2018 is the forty-ninth issue of this publication presenting a series of analytical national accounts tables for more than 200 countries and areas in the world. It has been prepared by the Statistics Division in cooperation with the national statistical offices. The publication presents, in the form of analytical tables, a summary of the principal national accounts aggregates as provided by countries and supplemented with estimates prepared by the Statistics Division. The tables of the publication include analysis of data on Gross Domestic Product (GDP) by different structural components, for example, by type of expenditure, kind of economic activity, major area, region and country as well as per capita and as growth rates.